Double Dividend from Tariff Differentiation of Reforestation Fund - Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2013)
Distortionary levy applied uniformly to all diameter classes of logs from logging natural forest can lead to inefficiencies; certain diameter should be left in the field because it is not economical to be used. Win-win or Pareto improving solution can be achieved if the government is more flexible. Social welfare is higher because of the waste that can be utilized to create employment, production and additional benefits for employers, as well as revenue for the state. Even if the levy rates are forced to zero for small-diameter timber, governments is actually not harmed at all because from the beginning the government does not get any revenue from small timber that is left in the field as waste. In scarcity situations of timber from natural forests, it is desirable if the government is considering differentiating charges in order to reduce or possibly eliminate the volume of waste generated by the levy. In general, tariff differentiation done in the form of higher tariffs for higher diameter logs. If possible, the lowest diameter limit of logs is forced down to its technical limits. That is, the processing tool that will determine how the minimum diameter logs can be processed profitably.Keywords: tariff differentiation, efficiency, timber utilization, government revenue, win-win solutionDOI: 10.7226/jtfm.19.2.163